The problem of over-age students in the Haitian education system: An overview - Haiti. Ministry of Education, Youth and Sports. Directorate of Planning and External Cooperation (Office of the UNESCO Representative in the Caribbean, 2000)
This monograph describes the main aspects of the problem with respect to over-age students in schools in Haiti. Following an overview of the Haitian education system, statistics and comments on the main aspects of the problem are presented, after which an attempt is made to describe the emergence of this category of students in the education system. Some of the effect of this phenomenon on the proper functioning of the education system are also presented.
Keywords: Over-age students